Precision medicine in clinical oncology: the journey from IgG antibody to IgE. Issue 3 (June 2020) - Fazekas-Singer, Judit; Singer, Josef; Jensen-Jarolim, Erika
Abstract : Purpose of review: Cancer is one of the leading causes of death and the incidence rates are constantly rising. The heterogeneity of tumors poses a big challenge for the treatment of the disease and natural antibodies additionally affect disease progression. The introduction of engineered mAbs for anticancer immunotherapies has substantially improved progression-free and overall survival of cancer patients, but little efforts have been made to exploit other antibody isotypes than IgG. Recent findings: In order to improve these therapies, 'next-generation antibodies' were engineered to enhance a specific feature of classical antibodies and form a group of highly effective and precise therapy compounds. Advanced antibody approaches include among others antibody-drug conjugates, glyco-engineered and Fc-engineered antibodies, antibody fragments, radioimmunotherapy compounds, bispecific antibodies and alternative (non-IgG) immunoglobulin classes, especially IgE. Summary: The current review describes solutions for the needs of next-generation antibody therapies through different approaches. Careful selection of the best-suited engineering methodology is a key factor in developing personalized, more specific and more efficient mAbs against cancer to improve the outcomes of cancer patients. We highlight here the large evidence of IgE exploiting a highly cytotoxic effector arm as potential next-generation anticancer immunotherapy.